RESOURCE-SAVING TECHNOLOGY OF MODIFICATION OF MALLEABLE CAST IRON CASTINGS - N. I. Urbanovich; O. S. Komarov; V. I. Volosatikov; D. O. Komarov; I. B. Provorova; V. S. Niss; V. A. Hatskevich (Литьë и металлургия)
It is shown that the used bismuth-molybdenum catalyst can serve as an effective additive in composition of the complex malleable cast iron modifier, which allows to reduce the cost of modifier and castings.